Efficacy and safety of crizotinib in patients with ROS1 rearranged non-small cell lung cancer: a retrospective analysis - Masuda, Ken; Fujiwara, Yutaka; Shinno, Yuki; Mizuno, Takaaki; Sato, Jun; Morita, Ryo; Matsumoto, Yuji; Murakami, Shuji; Goto, Yasushi; Kanda, Shintaro; Horinouchi, Hidehito; Yamamoto, Noboru; et al. (Journal of Thoracic Disease, 2019)
Background: Tyrosine kinase inhibitors (TKIs) are remarkably effective in patients with non-small cell lung carcinoma (NSCLC) harboring driver gene mutations and rearrangements. Crizotinib, a small-molecule TKI, has been demonstrated to be an efficacious drug against c-ros oncogene 1-rearranged NSCLC (ROS1-NSCLC) in clinical trials. However, information regarding the use of crizotinib in clinical practice in Japan is limited. Methods: Subjects with a definite diagnosis of advanced/relapsed ROS1-NSCLC were selected from consecutive NSCLC patients treated at the National Cancer Center Hospital between December 2014 and May 2018. We retrospectively assessed the efficacy and safety of crizotinib in clinical practice. Results: Among 24 patients with ROS1-NSCLC, the ROS1 rearrangement status was assessed using reverse transcription polymerase chain reaction (RT-PCR) (n=17), fluorescence in situ hybridization (FISH) (n=8), or next-generation sequencing (n=5) (some overlap occurred). Thirteen patients were treated with crizotinib in clinical practice. Among the 10 patients in whom clinical efficacy could be evaluated, the objective response rate (ORR) was 80.0% [95% confidence interval (CI), 49.0 to 94.3]. The median follow-up time was 35.5 months (95% CI, 8.9 to 44.6), the median progression-free survival (PFS) time was 10.0 months (95% CI, 5.1 to 27.0), and the median overall survival (OS) time was 28.7 months (95% CI, 6.7 to not reached). The most common adverse events were an aspartate/alanine aminotransferase (AST/ALT) increased and vision disorder. No severe adverse events related to crizotinib occurred. Conclusions: The use of crizotinib in patients with ROS1-NSCLC was effective and well tolerated in clinical practice in Japan without severe adverse events.